2022
DOI: 10.1021/acscatal.2c02849
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Photo-Oxidation of Water and Hole Scavengers on Hematite Photoanodes: Photoelectrochemical and Operando Raman Spectroelectrochemistry Study

Abstract: Hematite (α-Fe 2 O 3 ) is one of the most studied photoanode materials due to its stability in alkaline electrolytes and visible light absorption. However, its reported performance lags significantly behind its theoretical limit. Toward determining routes for efficient photo-oxidation on hematite, we investigated the role of hole-trapping surface states as reaction intermediates using sacrificial reductant reagents as hole scavengers, H 2 O 2 and FeCN. Photoelectrochemical characterization at low scavenger con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…14 The positive sides of S2 can be highlighted with sulfite oxidation, which is more kinetically favorable than water oxidation. 34 Following the results shown in Figures 2c and 3b, S1 was passivated in the presence of Na 2 SO 3 because of alteration on surface radical species, 35 and S2 became the main pathway for charge transfer for sulfite oxidation (illustrated in Figure 4b). Since the holes trapped in S2 had a lifetime much longer than those in S1, α-Fe 2 O 3 showed excellent PEC performance with an E on close to its flat band potential (Figure 1b).…”
Section: ■ Results and Discussionmentioning
confidence: 54%
“…14 The positive sides of S2 can be highlighted with sulfite oxidation, which is more kinetically favorable than water oxidation. 34 Following the results shown in Figures 2c and 3b, S1 was passivated in the presence of Na 2 SO 3 because of alteration on surface radical species, 35 and S2 became the main pathway for charge transfer for sulfite oxidation (illustrated in Figure 4b). Since the holes trapped in S2 had a lifetime much longer than those in S1, α-Fe 2 O 3 showed excellent PEC performance with an E on close to its flat band potential (Figure 1b).…”
Section: ■ Results and Discussionmentioning
confidence: 54%
“…As it shows, the peaks are indexed to hematite completely. 45 The Raman shift of Nb:Fe 2 O 3 locates almost the same as those of Fe 2 O 3 , but the peaks of FeSe 2 /Nb:Fe 2 O 3 exhibit a positive shift compared to that of Nb:Fe 2 O 3 . It is attributable to the lessened oxygen vacancy defects after surface treatment.…”
Section: Resultsmentioning
confidence: 81%
“…Raman spectra in Figure5dfurther proves that. As it shows, the peaks are indexed to hematite completely 45. The Raman shift of Nb:Fe 2 O 3 locates almost the same as those of Fe 2 O 3 , but the peaks of FeSe 2 /Nb:Fe 2 O 3 exhibit a positive shift compared to that of Nb:Fe 2 O 3 .…”
mentioning
confidence: 79%
“…Note that the notch/LWP filters installed in any Raman setup dedicated to the detection of the Stokes lines and used to suppress the Rayleigh line can also serve this purpose, depending on the specifications of the particular optical analysis system in use. Adopting this approach, Ramakrishnan and coworkers recently investigated the role of hole-trapping surface states in hematite photoanodes as reaction intermediates using sacrificial reducing compounds such as H 2 O 2 and FeCN as hole scavengers [54]. Using operando RS coupled with a PEC investigation of the system above, the authors observed a competitive photo-oxidation between H 2 O 2 , FeCN, and water at low scavenger concentrations and intermediate potentials.…”
Section: State Of the Art Of Operando Rs Of Semiconducting Photoelect...mentioning
confidence: 99%
“…To the best of our knowledge, only one report of semiconducting photoelectrodes and devices for photoelectrochemistry using in situ and operando RS exists. Recently, Ramakrishnan et al reported a competitive photo-oxidation of water and hole scavengers on hematite photoelectrodes using operando RS [54]. A similar approach was conducted in studying a PEC dye-sensitized solar cell, directly detecting charge transfer processes [55].…”
Section: Introductionmentioning
confidence: 99%